Sowur (House) Residential Space System, in the Eucalyptus Oil Industry in Wasur Village, Merauke, South Papua - Cindy Priscillia Sinay; Tarcicius Yoyok Wahyu Subroto (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to analyze the factors that influence the residential spatial system of the Marori and Mengge ethnic groups in Wasur Village, Merauke, South Papua, in the context of their involvement in the eucalyptus oil industry as a leading tourism product of Wasur National Park. A rationalistic qualitative approach is used with the main theory of behavioral setting to examine the relationship between behavior, local culture, and spatial structure. The results of the study indicate that houses not only function as domestic spaces, but also as places for the production of eucalyptus oil, especially at the packaging stage. The overlapping use of space causes space invasion, changes in function, and the emergence of high spatial flexibility. The space of the house undergoes a temporal functional transformation, adjusting to the intensity of economic activities and cultural rituals of the community. Private, semi-public, and spiritual spaces experience shifting boundaries, which have an impact on social relationship patterns and living comfort. This study also found that social structure, customary values (Boan/marga), and division of customary areas play an important role in the formation of the spatial system. These findings are expected to be an important contribution to the development of residential architecture based on behavior and local wisdom, as well as community-based conservation area management. This study also highlights the urgency of preserving the culture and existence of indigenous tribes amidst the current of modernization and the threat of extinction.